Airborne measurements of greenhouse gases during AAMP98 - Satoshi Sugawara; Shinji Morimoto; Shuji Aoki; Takakiyo Nakazawa (National Institute of Polar Research, 2002)
Air samples collected using aircraft during the Arctic Airborne Measurement Program 1998 (AAMP 98) were analyzed for the CO2, CH4, N20, and CO concentrations as well as for the carbon and oxygen isotopic ratios，δ^13C and δ^18O,of CO2, and δ^13C of CH4. The vertical distributions of CO2, CH4, N2O, and CO concentrations showed rapid decreases from the tropopause to the lower stratosphere over Ny-Alesund and Barrow. From the measured values of the CH4 concentration and δ^13C, the apparent carbon isotopic fractionation factor was estimated to be 1.013 （士0.003) in the lower stratosphere. The contributions of the chemical CH4 reactions with OH, O(^1 D) and Cl were examined by using the isotopic fractionation factors. It is suggested from this examination that the contribution of the reaction of CH4 with Cl is 12-17%.